Nonverbal components in communication: types of greeting - Yeshimov М.П.; Nurtileuova С.Р.; Mussayeva Г.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article reveals the number and meaning of nonverbal techniques used in communication. Although certain techniques in communication are not similar in terms of meaning, in everyday life they are used in some sense from the point of semantics view. At the same time, a number and meaning of nonverbal techniques used in communication are determined. Nonverbal communication tricks are performed through various parts of the body, giving different meanings. For example, a nod, a handshake, a knock, a hand raising, kissing, waving, etc. - such nonverbal techniques mean a greeting. In communication, such gestures are often used in everyday life. Of course, a person cannot communicate without using gestures when he enters into a relationship, because nonverbal techniques is a system of signs that clarify the meanings of gestures that give additional meaning and contribute to a more accurate and clear expression of thought. The authors argue that, although gestures in the greeting ritual in communication are not similar in terms of use, from the point of semantics view, meanings are transmitted through various non-verbal techniques. Including a handshake, a nod, etc., gestures transmitted by body parts have the same meaning among many people; that is, there are national gestures in the greeting ritual. Nonverbal techniques used in the greeting ritual in communication were analyzed on specific examples from works of art.